Strategic capabilities, innovation strategy and the performance of food and beverage small and medium enterprises - Salisu, Yakubu (2019)
The main objective of this study is to examine the mediating role of innovation strategy on the relationship between strategic capabilities and the performance of Small and Medium Enterprises (SMEs) in the Food and Beverage (F&B) industry. Strategic capabilities, as a construct in this study, consist of top management capability, technological capability, learning capability and relational capability. Equally in the construct are innovation strategy and SMEs performance. After reviewing the available relevant literature on strategic capabilities and innovation strategy, a conceptual framework was developed based on the Resource Based View (RBV) and Dynamic Capability Theory (DCT). Based on the model developed, a questionnaire was constructed and personally administered at random to collect the data from 229 respondents in the study area. Algorithm and bootstrapping techniques of Partial Least Squared Structural Equation Model (Smart PLS-3.0) was used to test the developed hypotheses of the study. The statistical results of the test supported most of the relationship hypothesized for the study. Top management and technological capabilities positively and significantly relates to F&B SMEs performance. Similarly, top management, technological, learning and relational capabilities significantly and positively related to SMEs innovation strategy. Innovation strategy positively impacted on performance. However, no significant relationship between learning capability, relational capability and SMEs performance was established. Moreover, significant mediation effect was established for all the four hypotheses. Consequently, the significant positive impacts of top management, technological, learning and relational capabilities postulate that these variables are valuable in influencing performance directly and indirectly through innovation strategy. On this note, F&B SMEs’ managers are encouraged to develop and maintain these strategic capabilities for outstanding performance. The results of this research have contributed significantly to the body of existing literature, provided a guide to managers and policies makers, and proffered suggestion for future research based on limitation of the study.